2019
DOI: 10.1371/journal.pone.0214787
|View full text |Cite
|
Sign up to set email alerts
|

Neonicotinoid insecticide residues in subsurface drainage and open ditch water around maize fields in southwestern Ontario

Abstract: Neonicotinoids are widely used class of insecticides. Most are seed treatments and during planting active ingredient may be abraded and lost in fugitive dust. Much of this active ingredient contaminates surface waters, exposing aquatic organism to potential ill effects. This study examines concentrations of neonicotinoids appearing in tile drains and open ditches around commercial maize fields around planting time where neonicotinoid seed treatments had been used. This sample set represents surface water leavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The results also showed that neonicotinoids could be detected at more sampling points in November 2020 (eight locations) than in August 2021 (four locations) ( Figure 1 ). This may have been because the rainy season occurs in November, causing the release of neonicotinoids stored in soils after the previous rice cultivation season into rivers/creeks through runoff after rainfall events ( Sánchez-Bayo and Hyne, 2014 ; Schaafsma et al., 2019 ; Zhang et al., 2019 ). Rainfall also increases the turbidity of water, thus preventing the photodegradation process of neonicotinoids in water ( Sánchez-Bayo and Hyne, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results also showed that neonicotinoids could be detected at more sampling points in November 2020 (eight locations) than in August 2021 (four locations) ( Figure 1 ). This may have been because the rainy season occurs in November, causing the release of neonicotinoids stored in soils after the previous rice cultivation season into rivers/creeks through runoff after rainfall events ( Sánchez-Bayo and Hyne, 2014 ; Schaafsma et al., 2019 ; Zhang et al., 2019 ). Rainfall also increases the turbidity of water, thus preventing the photodegradation process of neonicotinoids in water ( Sánchez-Bayo and Hyne, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sample collection was performed using a stainless-steel bucket attached to a rope. The sample collection method followed the methods of Schaafsma et al. (2019) with some modifications.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…About the active ingredient applied to the seed, only approximately 5% is taken up by the crop while most of it remains in the soil and leaches to ground/surface waters [36][37][38][39][40][41][42][43]. Furthermore, the drilling machine used for sowing releases into the atmosphere particulate matter produced from abrasion of seed coatings, that contains 1-2% of the total amount of pesticide applied in the field [44].…”
Section: Introductionmentioning
confidence: 99%